2007
DOI: 10.4049/jimmunol.178.11.7211
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional CTL Avidity/Activity Compartmentalization to the Site of Mucosal Immunization Contributes to Protection of Macaques against Simian/Human Immunodeficiency Viral Depletion of Mucosal CD4+ T Cells

Abstract: The presence of high-avidity CTLs in the right compartment can greatly affect clearance of a virus infection (for example, AIDS viral infection of and dissemination from mucosa). Comparing mucosal vs systemic immunization, we observed a novel compartmentalization of CTL avidity and proportion of functionally active Ag-specific CD8+ T cells to tissues proximal to sites of immunization. Whereas both s.c. and intrarectal routes of immunization induced tetramer+ cells in the spleen and gut, the mucosal vaccine ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 77 publications
7
100
0
Order By: Relevance
“…Consistent findings were observed in our previous studies where, of two cohorts of SIV/HIV-infected macaques, one of four in the first cohort (4,36) and three of four in the second cohort (5) in the adjuvant-only group failed to get infected. We identified that the enhanced A3G expression was widely distributed in DCs, monocyte/macrophage, and CD4 + T cells.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent findings were observed in our previous studies where, of two cohorts of SIV/HIV-infected macaques, one of four in the first cohort (4,36) and three of four in the second cohort (5) in the adjuvant-only group failed to get infected. We identified that the enhanced A3G expression was widely distributed in DCs, monocyte/macrophage, and CD4 + T cells.…”
Section: Discussionsupporting
confidence: 76%
“…IFN-␥ production in T cells was measured after restimulated with proper peptides. Intracellular cytokines was measured in DCs after stimulation with TLR ligands (49). ELISA or multiplex systems were used to determine cytokine production in DC supernatants.…”
Section: Animals and Reagentsmentioning
confidence: 99%
“…However, generation and survival of antigen-specific CD8 1 T cells after i.r. immunization is not well understood [10,51,52]. In this study, we continued to characterize: (i) the kinetics of CD8 1 T-cell responses in the gut after i.r.…”
Section: Discussionmentioning
confidence: 99%
“…SI-IEL cells and LP lymphocytes from mice were isolated as described previously with a minor modification [52].…”
Section: Viruses and Immunization Protocolmentioning
confidence: 99%